PARTICIPATORY BUDGETING PADA ALOKASI DANA DESA DI DESA SIMPANG KOTA MEDAN KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU TAHUN 2021 - Wulandari, Triana; Handoko, Tito (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Participatory budgeting is a process where the community can contribute to budget decision making and the community is also actively involved in formulating agendas based on real needs which are then agreed to be priorities that will be implemented. Participatory budgeting in budget planning will produce development activities that suit community needs. The research method used in this research is a qualitative method with a descriptive approach. The data collection technique uses interview and documentation methods. The data analysis process includes data reduction, data presentation, and drawing conclusions. The research location is Simpang Village, Medan City. This research found that the application of participatory budgeting in the Village Fund Allocation (ADD) in Simpang Village, Medan City, Kelayang District, Indragiri Hulu Regency in 2021 has not been implemented well. The relatively low level of community participation in involvement in ADD budget planning can be seen in the RKPDes musrenbangdes so that meeting community needs is not realized optimally. On the other hand, there are transparency efforts by the village government in financial management in fulfilling open access in information media to avoid budget misappropriation. The aspect of community involvement in the process has not been specifically regulated by a Village Regulation, however the village government has been guided by Indragiri Hulu Regency Regional Regulation Number 12 of 2020 in initiating community involvement. Apart from that, community involvement also includes the regional/physical dimension. This is reflected in the existence of deliberations at the hamlet level. Keywords: Participatory Budgeting, Village fund allocation